ANALYSIS OF PECULIARITIES OF NATIONAL PAYMENT SYSTEMS FUNCTIONING AND CURRENT PAYMENT VOLUMES - Oteshova, Almagul; Prodanova, Natalia; Dikikh, Vadim; Savina, Natalia (Humanities & Social Sciences Reviews, 2020)
Purpose of the study: In current conditions of globalization, the role and importance of non-cash payment systems have changed dramatically. The authors of the article are aiming to analyze and promote new banking products and describe the way of development of modern banking business trends in the field of electronic banking services in their article. Methodology: In the course of this study, methods of comparative and statistical analysis, empirical, interviewing, observation and economic, and mathematical modeling were used. Main Findings: The Central payment systems of the Republic of Kazakhstan provides options for the needs of the real economy sector, financial markets, and banks the other participants in the late payments and money transfers, as well as contribute to the effective implementation of monetary policy and the execution of the state budget. Applications of this study: The theoretical and practical provisions of the research can be applied in the educational process in economic areas and banking organizations’ activities. Calculations are a necessary accompanying element of the money supply’s creation (withdrawal) as a derivative of money circulation and one of the monetary regulation’s main objects. Novelty/Originality of this study: Development of theoretical provisions aimed to modernize the mechanisms of state regulation of the domestic national payment system. It ensures its further development in current conditions and the formulation of practical recommendations and justification of organizational tools.